Strategic Role of Corporate Social Responsibility in Mitigating Air Pollution: A Case Study of PT Pertamina (Persero) Refinery Unit II Dumai - Yogia, Moris Adidi; Wedayanti, Made Devi; Pulungan, Boby Indra; Prihatin, Panca Setyo (Journal Public Policy, 2025)
This study examines the role of Corporate Social Responsibility (CSR) in addressing environmental challenges, particularly air pollution, by PT Pertamina (Persero) Refinery Unit II in Dumai City. The research aims to assess how the company’s CSR initiatives contribute to mitigating negative environmental impacts while fostering sustainable development in its operational area. Employing a qualitative research design, data were collected through interviews and document analysis, then processed using NVivo 12 for thematic analysis. The findings reveal that PT Pertamina’s CSR implementation is structured around three core strategies: leadership commitment, regional outreach, and stakeholder engagement. Among these, stakeholder engagement was identified as the most significant factor in strengthening the effectiveness of CSR practices, especially in building community trust and promoting cooperative problem-solving related to air pollution. The study also highlights that CSR is not merely a legal or ethical obligation but functions as a strategic mechanism for social welfare improvement and long-term business sustainability. However, this research is limited by its qualitative focus, which does not include direct environmental data or broad community-based surveys. Future studies are recommended to integrate quantitative environmental metrics and expand stakeholder representation to enhance the reliability and policy relevance of CSR evaluations in the context of environmental management.